Induced shifting involvements and cycles of growth and distribution - Michalis Nikiforos (Levy Economics Institute of Bard College, 2019)
The paper builds on the concept of (shifting) involvements, originally proposed by Albert Hirschman (2002 [1982]). However, unlike Hirschman, the concept is framed in class terms. A model is presented where income distribution is determined by the involvement of the two classes, capitalists and workers. Higher involvement by capitalists and lower involvement by workers tends to increase the profit share and vice versa. In turn, shifts in involvements are induced by the potential effect of a change in distribution on economic activity and past levels of distribution. On the other hand, as the profit share increases, the economy tends to become more wage led. The dynamics of the resulting model are interesting. The more the two classes prioritize the increase of their income share over economic activity, the more possible it is that the economy is unstable. Under the stable configuration, the most likely outcome is Polanyian predator-prey cycles, which can explain some interesting historical episodes during the 20th century. Finally, the paper discusses the possibility of conflict and cooperation within each of the distribution-led regimes.
Keywords: E11; E12; E21; E22; E32; 330; Shifting Involvements; Hirschman; Wage Led; Profit Led; Predator-Prey